An atomic model of HIV-1 capsid-SP1 reveals structures regulating assembly and maturation - Schur, Florian Konstantin Michael; Obr, Martin; Kräusslich, Hans-Georg; Briggs, John A. G. (Science, 2016)
Immature HIV-1 assembles at, and buds from, the plasma membrane before proteolytic cleavage of the viral Gag polyprotein induces structural maturation. Maturation is blocked by protease and maturation inhibitors (MIs), abolishing infectivity. The CA (capsid) and SP1 (spacer peptide 1) region of Gag is the key regulator of assembly and maturation, and the target of MIs. Here we applied optimized cryo-electron tomography and subtomogram averaging to resolve this region within assembled immature HIV-1 particles at 3.9 Å resolution and built an atomic model. The structure reveals a network of intra- and inter-molecular interactions mediating immature HIV-1 assembly. The proteolytic cleavage site between CA and SP1 is inaccessible to protease. We suggest that MIs prevent CA-SP1 cleavage by stabilizing the structure, and MI resistance develops by destabilizing CA-SP1.
Gesehen am 04.01.2019